Rapid preparation method of cryogenic-resistant low-thermal-conductivity alumina fiber resin-based composite material
By multi-gradient sintering and water-based epoxy sizing treatment of alumina fiber filaments, combined with roller arrangement and autoclave molding, the problems of high thermal conductivity and high preparation cost of traditional composite materials in ultra-low temperature environments are solved, and low-cost and rapid preparation of high-performance alumina fiber resin-based composite materials is achieved, which is suitable for the thermal insulation support structure of superconducting electromagnetic equipment.
Patent Information
- Application Number
- CN202510604149.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-09-16
AI Technical Summary
Existing carbon fiber and glass fiber reinforced composite materials have high thermal conductivity in ultra-low temperature environments and cannot meet the thermal insulation requirements of superconducting magnets. In addition, traditional prepreg equipment is expensive and occupies a large area, making it difficult to quickly prepare small-width materials.
Alumina fiber resin-based composite materials are prepared by using multi-gradient sintered alumina fiber filaments, which are impregnated with a water-based epoxy sizing agent and dried before twist-free spinning. Low-viscosity resin and conventional resin are used to achieve small-batch rapid preparation through a winding machine and a flat mold.
The rapid preparation of low thermal conductivity alumina fiber resin-based composite materials has been achieved, which reduces the waste rate and improves material utilization and strength. It is suitable for the thermal insulation support structure of superconducting electromagnetic equipment, is low-cost and suitable for small-batch testing.
Smart Images

Figure CN120645470A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparing resin-based composite materials, and in particular to a method for rapidly preparing a deep-cold-resistant and low-thermal-conductivity alumina fiber resin-based composite material. Background Art
[0002] For ultra-high-speed vacuum tube magnetic levitation transportation systems, the core power comes from low-temperature / high-temperature superconducting magnets. The key thermal insulation and load-bearing composite material structure requires materials with extremely strong thermal insulation and extremely high load-bearing performance at ultra-low temperatures (10K~100K). Although the existing traditional carbon fiber reinforced composite materials (Carbon Fiber Reinforced Polymer / Plastic, CFRP) and glass fiber reinforced plastics (Glass Fiber Reinforced Plastic, GFRP) meet the mechanical properties requirements, their high thermal conductivity still cannot meet the heat leakage requirements of superconducting magnets in the liquid helium temperature range. Their comprehensive mechanical and thermal performance is seriously insufficient. There is an urgent need for a new resin-based composite material with good comprehensive mechanical and thermal performance in deep-cold environments to replace traditional CFRP and GFRP materials.
[0003] In addition, to obtain composite materials with high mechanical and thermal properties, it is necessary to adopt a prepreg laying process in conjunction with an autoclave curing industry, which is also a key process in the entire composite preparation process. Traditional professional dry prepreg equipment occupies a large area, has high equipment investment costs, and has a width of only 1000mm or above. For preliminary research on new materials such as resin alumina composite materials, a small width is required, which is extremely unfriendly to the scenario of rapid preparation and iteration. There is an urgent need for a method to quickly and low-cost prepare high-performance fiber-reinforced resin-based composite materials. Summary of the Invention
[0004] The present invention provides a method for rapidly preparing a deep-cold-resistant, low-thermal-conductivity alumina fiber resin-based composite material, which can address the technical gap in the preparation process of high-strength, low-thermal-conductivity resin-based continuous alumina fiber prepregs and their composite materials for ultra-low-temperature and deep-cold environments, and solve the problems of expensive dry prepreg equipment, long prepreg preparation cycle, and easy fuzzing and breakage of brittle ceramic alumina fibers after sizing.
[0005] According to one aspect of the present invention, a method for rapidly preparing a deep-cold-resistant, low-thermal-conductivity alumina fiber resin-based composite material is provided, the method comprising:
[0006] Alumina fiber filaments are subjected to multi-gradient sintering and cooled to a first preset temperature, and the cooled alumina fiber filaments are infiltrated with a water-based epoxy sizing agent. After the infiltration is completed, the alumina fiber filaments are dried to obtain alumina fiber filaments with a resin layer wrapped on the surface; wherein the water-based epoxy sizing agent is composed of a water-based epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or is composed of polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyethylene solution with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37%, and the solvent is water; during the infiltration process, the wire speed range is 1 to 1.5 m / min, and the water-based epoxy sizing agent is kept in a uniformly mixed state by stirring; during the drying process, the drying temperature range is 148° C. to 155° C., and the drying time range is 3 to 5 minutes;
[0007] Alumina fiber filaments coated with a resin layer are subjected to twist-free spinning to obtain flat-head fiber bundles;
[0008] A drum with a preset diameter is mounted on a drum-type arrangement machine, and a release paper or liner is laid on the outer surface of the drum; a flat-head fiber tow is spirally wound on the drum with the release paper or liner to obtain a wound drum tow;
[0009] Use multi-component resin mix or single-component resin as prepreg film or ready-to-dip;
[0010] The prepreg film is laminated with the drum tow wound on the drum for dipping, and then hot-pressed to achieve semi-curing treatment; or the drum tow wound on the drum is placed in the prepared dipping glue and rotated, and the surface of the drum tow is brushed with glue to ensure uniform bonding of the fibers and the glue, and then placed in an oven for semi-curing treatment according to the preset temperature and time;
[0011] After the semi-curing treatment, PE film paper is pasted on the outer surface of the drum tow, and the drum tow is cut along the drum generatrix to obtain prepreg;
[0012] A plurality of prepregs of preset shapes are cut out from the prepreg cooled to a second preset temperature, the cut prepregs are laid out according to preset laying angles and numbers of layers, and the laid prepregs are cured to obtain an alumina fiber resin-based composite material.
[0013] Preferably, the thickness of the resin layer on the surface of the alumina fiber filaments is greater than the thickness of the carbon fiber and the glass fiber.
[0014] Preferably, the alumina fiber is a low-temperature alumina fiber, the temperature range of the low-temperature alumina fiber is -269 to -100 ° C, and the density range is 3.2-3.4 g / cm 3, diameter range is 11-14μm, and elongation at break range is 0.75~0.85%.
[0015] Preferably, the width of the flat head fiber tow is in the range of 3 to 5 mm, and the tow range is in the range of 0.1 to 4K.
[0016] Preferably, the surface of the release paper or the liner is coated with an isolation material.
[0017] Preferably, during the winding process, if there is a defective yarn bundle, determine whether the length of the defective position is greater than the circumference of the drum. If so, cut off the defective yarn bundle and start winding again. Otherwise, continue winding and mark the defective position, and avoid the marked defective position when cutting the prepreg.
[0018] Preferably, the multi-component resin includes a low-viscosity resin and a normal-viscosity resin, wherein the viscosity of the low-viscosity resin is in the range of 200 to 1000 mPa·s, and the viscosity of the normal-viscosity resin is in the range of greater than 1000 mPa·s.
[0019] Preferably, a plurality of prepregs of preset shapes are cut out from the prepreg, the cut prepregs are laid out according to preset lay-up angles and numbers of layers, and the laid prepregs are cured to obtain the alumina fiber resin-based composite material, which includes:
[0020] Cutting a plurality of prepregs of preset shapes from the prepreg;
[0021] Perform surface treatment on the two molds of preset shapes and apply release agent or lay release cloth;
[0022] Tear off the release paper or liner from the cut prepregs and lay them layer by layer on one of the molds according to the preset laying angle. During the laying process, press each layer evenly with a flat plate or a tool that fits the shape, tear off the PE film on the other side, and continue laying. After laying every 5-10 layers, use a vacuum bag to evacuate the air between the layers and press them tightly and evenly.
[0023] After the prepreg is laid out and evacuated with a vacuum bag, another mold cover is placed on the upper surface and placed in an autoclave for curing. After the curing is completed, the mold is removed to obtain an alumina fiber resin-based composite material.
[0024] According to another aspect of the present invention, a deep-cold-resistant low-thermal-conductivity alumina fiber resin-based composite material is provided, and the deep-cold-resistant low-thermal-conductivity alumina fiber resin-based composite material is prepared by any of the above-mentioned methods.
[0025] Compared with the prior art, the application of the technical solution of the present invention has the following beneficial effects:
[0026] 1. Alumina fiber filaments are impregnated with a water-based epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or a water-based epoxy sizing agent composed of a polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyethylene solution with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37%. This can achieve a fuzzing amount of 4K continuous alumina fiber tow ≤ 1.3 mg / 50 m, reduce the waste rate, increase the utilization rate, and improve the quality and strength of the prepreg;
[0027] 2. The existing winding machine equipment with a price of about RMB 100,000 to 200,000 can be used in conjunction with the designed roller tooling and flat tooling molds. The cost is low and no expensive yarn spreading dry prepreg equipment is required. The width can be flexibly customized according to small batch tests, such as 300mm width, 400mm width, etc., without being limited by the width of professional prepreg equipment, such as 1000mm.
[0028] 3. It can use wet winding low viscosity resin or conventional standard professional prepreg resin, and the resin selection is flexible;
[0029] 4. It can quickly prepare small batches of test pieces and products for testing the basic mechanical and thermal properties of resin-based alumina composites, as well as for resin selection and matching, fiber performance confirmation, and iterative optimization of composite interface bonding performance. It is suitable for rapid iterative testing in the early pre-research stage. From material preparation to composite sample preparation, it can be completed within 1-2 weeks.
[0030] 5. The use of autoclave molding makes the composite layers denser, the interlayer strength is improved, the interlayer strength is maximized, the overall defects are few, the porosity can be controlled to within 2-4%, there are no defects such as delamination and looseness, the mechanical properties are high, and it is suitable for the preparation of main load-bearing structures;
[0031] 6. The formed resin alumina composite material AluminaFRP has high mechanical properties and strong ultra-low temperature thermal insulation performance. It can replace traditional CFRP and GFRP and is very suitable for the preparation of thermal insulation support structures for low-temperature and deep-cold application scenarios such as superconducting electromagnetic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings are included to provide a further understanding of the embodiments of the present invention, constitute a part of the specification, illustrate the embodiments of the present invention, and together with the description, explain the principles of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and those skilled in the art can derive other drawings based on these drawings without inventive effort.
[0033] Figure 1A flow chart of a prepreg preparation process according to an embodiment of the present invention is shown;
[0034] Figure 2 A flow chart showing a process for preparing an alumina fiber resin-based composite material by autoclave molding according to an embodiment of the present invention is shown;
[0035] Figure 3 A comparison diagram of thermal conductivity between an alumina fiber resin-based composite material and CFRP provided according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0036] It should be noted that, in the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present invention and its application or use. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.
[0038] Unless otherwise specifically stated, the relative arrangement of the parts and steps, the numerical expressions and the numerical values set forth in these embodiments do not limit the scope of the present invention. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The techniques, methods and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the techniques, methods and equipment should be considered as part of the authorization specification. In all examples shown and discussed here, any specific values should be interpreted as being merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar numbers and letters represent similar items in the following figures, and therefore, once an item is defined in one figure, it does not need to be further discussed in subsequent figures.
[0039] like Figure 1 and Figure 2As shown, the present invention provides a method for rapidly preparing a deep-cold-resistant and low-thermal-conductivity alumina fiber resin-based composite material, the method comprising:
[0040] Alumina fiber filaments are subjected to multi-gradient sintering in a high-temperature sintering kiln and cooled to a first preset temperature (cooled to below 60°C), and the cooled alumina fiber filaments are infiltrated with a water-based epoxy sizing agent. After the infiltration is completed, the alumina fiber filaments are dried in a high-temperature furnace to obtain alumina fiber filaments with a resin layer wrapped on the surface; wherein the water-based epoxy sizing agent is composed of a water-based epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or a polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyvinyl alcohol with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37%. The invention relates to a method for preparing a sizing agent comprising an ethylene solution and a solvent comprising water. Specifically, polyvinyl alcohol (PVA) is a film-forming agent, mainly used for bonding and film-forming fibers, and a polyethylene solution is a fiber lubricant, mainly used for reducing fiber friction coefficient and improving fiber wear resistance. During the impregnation process, the wire speed ranges from 1 to 1.5 m / min, and the water-based epoxy sizing agent is kept in a uniformly mixed state by stirring. Specifically, the sizing agent can be continuously mixed uniformly under the action of a circulating pump. During the drying process, the drying temperature ranges from 148°C to 155°C, and the drying time ranges from 3 to 5 minutes. Since the density of the alumina fiber is in the range of 3.2-3.4 g / cm 3 , the diameter range is 11-14μm, the elongation at break range is 0.75-0.85%, it is a brittle ceramic fiber with high brittleness; therefore, in order to control the damage of the fiber filaments, the above-mentioned water-based epoxy sizing agent is used to implement the sizing process, which improves the fiber's bundling, processability, wear resistance, surface properties and interface strength properties after compounding with resin, so that the thickness of the resin layer on the surface of the brittle and rough surface alumina fiber filaments is greater than that of carbon fiber and glass fiber, avoiding damage to the fiber filaments, thereby obtaining an alumina fiber reinforced resin-based composite material with lower fuzzing and breaking rate and higher interface bonding properties; the two formulas have the same effect on improving wear resistance, removing fiber hair and fiber breakage, and the finished product color is slightly different. You can choose either one when implementing the actual process; this step is to prepare for the subsequent high-bundling, wear-resistant and low-fuzzing fibers;
[0041] Alumina fiber filaments coated with a resin layer are spun without twist to produce 3-5 mm flat-end fiber tows. The 3-5 mm flat-end fiber tows are made by plying multiple strands of 0.1-4K tows with a winding tension of 500±30 cN. By sizing the low-temperature alumina fiber filaments, damage to the yarns caused by frequent contact and friction during the prepreg preparation process is avoided, which ultimately leads to problems such as yarn splitting, breakage, and wear.
[0042] A drum of preset diameter is installed on a drum-type arrangement machine, and a release paper or liner is laid on the outer surface of the drum. The surface of the release paper or liner is coated with an isolation material to prevent adhesion when the prepreg is removed; the flat-head fiber tow is spirally wound on the drum covered with the release paper or liner to obtain a wound drum tow; wherein, during the winding process, if there is a defective tow (poor quality, breakage or curling), it is determined whether the length of the defective position is greater than the circumference of the drum. If so, the defective tow is cut off and the winding is restarted. Otherwise, the winding is continued and the defective position is marked. The marked defective position is avoided when the prepreg is cut; the drum diameter should be greater than 30mm to avoid being lower than the fiber bending and fracture radius;
[0043] A multi-component resin mixture or a single-component resin is used as a prepreg film or a pre-impregnated resin; wherein the multi-component resin includes a low-viscosity resin and a normal-viscosity resin, wherein the viscosity of the low-viscosity resin is in the range of 200 to 1000 mPa·s, and the viscosity of the normal-viscosity resin is in the range of greater than 1000 mPa·s;
[0044] The prepreg film is laminated with the drum tow wound on the drum for dipping, and then hot-pressed to achieve semi-curing treatment; or the drum tow wound on the drum is placed in the prepared dipping glue and rotated, and the surface of the drum tow is brushed with glue to ensure uniform bonding of the fibers and the glue, and then placed in an oven for semi-curing treatment according to the preset temperature and time; PE film paper is pasted on the outer surface of the drum tow after the semi-curing treatment, and the drum tow is cut along the drum busbar to obtain prepreg; the prepreg can be placed in a refrigerator for refrigeration (-18°C) for use in subsequent layering and composite material preparation;
[0045] The two molds of preset shapes are surface treated (sandblasting or surface anodizing), and mold release agent is applied or mold release cloth is laid; the prepreg is taken out to test its adhesive state, and several prepregs of preset shapes are cut out from the prepreg; the cut prepregs are laid layer by layer on one of the molds according to the preset laying angle, and the release paper or release paper is torn off. During the laying process, each layer needs to be pressed evenly with a flat plate or a tool that adapts to the shape, and the PE film on the other side is torn off, and the laying is continued. After laying 5-10 layers, a true The empty bag is evacuated to squeeze out the air between the layers, and the layers are compacted and evenly pressed. After the prepreg is evacuated with a vacuum bag, another mold cover is placed on the upper surface and placed in an autoclave for curing (the program is set according to the resin's factory curing curve, and the pressure is adjusted to 7-10 atmospheres). After the curing is completed, the mold is removed to obtain an alumina fiber resin-based composite material. Specifically, after the curing is completed, the external dimensions can be added by machine before demoulding, and the corresponding appearance, size, weight, non-destructive testing, etc. are carried out to complete the preparation of the composite material with the preset shape. Among them, the alumina fiber resin-based composite material is an alumina fiber reinforced resin-based composite material.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] 1. Alumina fiber filaments are impregnated with a water-based epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or a water-based epoxy sizing agent composed of a polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyethylene solution with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37%. This can achieve a fuzzing amount of 4K continuous alumina fiber tow ≤ 1.3 mg / 50 m, reduce the waste rate, increase the utilization rate, and improve the quality and strength of the prepreg;
[0048] 2. The existing winding machine equipment with a price of about RMB 100,000 to 200,000 can be used in conjunction with the designed roller tooling and flat tooling molds. The cost is low and no expensive yarn spreading dry prepreg equipment is required. The width can be flexibly customized according to small batch tests, such as 300mm width, 400mm width, etc., without being limited by the width of professional prepreg equipment, such as 1000mm.
[0049] 3. Both wet winding low-viscosity resin and conventional standard professional prepreg resin can be used, and the resin selection is flexible;
[0050] 4. It can quickly prepare small batches of test pieces and products for testing the basic mechanical and thermal properties of resin-based alumina composites, as well as for resin selection and matching, fiber performance confirmation, and iterative optimization of composite interface bonding performance. It is suitable for rapid iterative testing in the early pre-research stage. From material preparation to composite sample preparation, it can be completed within 1-2 weeks.
[0051] 5. The use of autoclave molding makes the composite layers denser, the interlayer strength is improved, the interlayer strength is maximized, the overall defects are few, the porosity can be controlled to within 2-4%, there are no defects such as delamination and looseness, the mechanical properties are high, and it is suitable for the preparation of main load-bearing structures;
[0052] 6. The formed resin alumina composite material AluminaFRP has high mechanical properties and strong ultra-low temperature thermal insulation performance. It can replace traditional CFRP and GFRP and is very suitable for the preparation of thermal insulation support structures for low-temperature and deep-cold application scenarios such as superconducting electromagnetic equipment.
[0053] The present invention also provides a deep-cold-resistant low-thermal-conductivity alumina fiber resin-based composite material, which is prepared by any of the above-mentioned methods.
[0054] In order to have a further understanding of the present invention, the following Figure 1-Figure 3 The rapid preparation method of the deep-cold-resistant and low-thermal-conductivity alumina fiber resin-based composite material of the present invention is described in detail.
[0055] In this embodiment, a prepreg is prepared and a mechanical tensile test piece is prepared according to GB / T 3354-2014 Test method for tensile properties of oriented fiber reinforced polymer matrix composite materials, specifically comprising the following steps:
[0056] Step 1: Fiber Preparation
[0057] The low-temperature and low-thermal-conductivity continuous alumina fiber (model: γ-Al2O3 continuous alumina fiber (gamma phase)) was sintered in multiple gradients using a high-temperature sintering kiln and cooled to below 60°C. The water-based sizing agent PEG20004K flat head was used and the winding tension was set to 500±30cN for spinning and winding. Then, the spinning was performed without twisting. A 100m×10 drum was prepared and installed on the winding machine. A 500mm diameter roller tooling was installed on the winding machine. According to the fiber volume fraction V required by the composite material, f =50%, calculate and set the rolling speed to 5r / min, set the corresponding roller axial feed speed, and set the tension to be the same as the winding tension of the yarn bobbin;
[0058] Step 2: Prepare prepreg film
[0059] Based on the calculated resin dosage, such as 35% by mass, the dipping is ready. Special processing methods are required to find the key temperature and time parameters for low-viscosity resins to cure to a semi-dry state. For example, IR3 low-temperature resin, the resin curing process is suitable for RTM, winding and other molding methods. The viscosity of this resin is extremely low for a long time in the low-temperature section, which is very different from the viscosity of the resin used in the conventional wet prepreg process. However, it has good ultra-low temperature resistance. Using it to prepare a semi-dry prepreg is one of the key technologies. Through the viscosity-temperature curve and the viscosity-time curve, the short-term 10 minutes, 15 minutes, 30 minutes and T1, T2, T3 are estimated. The first round of orthogonal experimental design with two factors and three levels is carried out, and the experiment is started. The purpose of the experiment is to find the appropriate time and temperature to return to room temperature or low-temperature refrigeration to reach a semi-dry state (50000~100000 mPa·s), it will become sticky again after being heated again, and it will have the basic mechanical properties of the resin body after multi-layer laying and curing. The test iteration of this method is estimated to take 1-2 weeks. After test optimization, for example, IR3 resin can be cured at 130℃ for 30 minutes to become semi-dry. After the laying is completed, it can be cured according to the curing process in the instructions. The temperature is raised from room temperature to 110℃ within 60 minutes, and this temperature (110℃) is kept constant for 5 hours. Then the temperature is raised from 110℃ to 125℃ within 30 minutes, and this temperature (125℃) is kept constant for 16 hours. The resin system is fully cured and finally cooled with the furnace. Conventional prepreg resin can reach the corresponding state according to the factory data. There is no need for excessive testing. It is only necessary to test and verify the factory resin viscosity, resin cross-linking curing temperature and other parameters.
[0060] In this example, IR3 low-viscosity resin was used. The melting and filming temperature was determined based on the viscosity-temperature and viscosity-time curves. Because this resin exhibits good fluidity and viscosity at room temperature, the three components, A, B, C, and C, were mixed at room temperature in a ratio of 100:102:21 and pre-impregnated onto the fibers on a roller. The goal was to uniformly infiltrate the resin film into the fiber sheet and then heat-press it for uniform impregnation. The impregnation speed was 1 r / min (a slower speed reduces friction between fibers and, combined with a thicker sizing layer, results in better impregnation). The pressure was 0.1 MPa, and the impregnation temperature was 23°C. Impurities were removed, and release paper was subsequently applied and semi-cured at 120°C for 5 minutes. After exiting the oven, the release paper was cut and PE film was applied. This yielded a prepreg with the appropriate adhesive content, free of bubbles and resin buildup. The prepreg was then refrigerated in a freezer (-18°C) for subsequent layering and composite preparation.
[0061] Step 3: Prepare the flat test piece
[0062] In the clean room, the surface of a 300mm×300mm flat mold was polished and coated with a release agent. After the prepreg was taken out and left for 30 minutes, its adhesive state was tested. When it was in a semi-dry adhesive state like a tape, it was laid according to the 0° tensile test piece designed for the composite material. After laying 5 layers, a vacuum bag was used for pre-compaction. The vacuum pressure was 0.1MPa to squeeze out the air between the layers and compact them. 20 layers (based on actual measurement experience, the thickness of each prepreg layer was 0.1mm, and a 2mm thick, 12.5mm wide and 250mm long test piece was laid. The thickness was 1mm, which was easy to cut) The test piece is destroyed, so it is set to 2mm). After the laying is completed, it is evacuated and pressed with a vacuum bag. It is fixed with two upper and lower flat molds and compacted and placed in an autoclave. According to the resin's factory curing curve, the program is set for 5 hours @ 110℃ and then maintained at 125℃ for 16 hours. The pressure is adjusted to 8 atmospheres and the curing molding begins. After completion, the temperature is cooled to room temperature with the furnace. Five test pieces are cut using a machine tool or a water jet to complete the preparation of low-cost resin alumina composites. The mechanical strength can reach more than 1000MPa and the modulus is 110±5GPa, which is 2-3 times that of general GFRP materials and comparable to CFRP.
[0063] In this example, six 40×40×4 mm test pieces were prepared. According to GB / T32064-2015, the parallel thermal conductivity was measured using a low-temperature vacuum dewar, a GM refrigerator, a molecular pump, a temperature control device, and a thermal constant analyzer HotDisk. The thermal conductivity was compared with that of conventional T700 / epoxy at ultra-low temperatures, and the data were as follows: Figure 3 As shown, in Figure 3The thermal conductivity of the prepared resin alumina is much lower than that of CFRP at ultra-low temperatures, making it the preferred thermal insulation support material for low-temperature equipment structures such as superconducting electromagnetics.
[0064] In summary, the present invention provides a method for rapidly preparing a deep-cold-resistant, low-thermal-conductivity alumina fiber resin-based composite material, which has the following beneficial effects:
[0065] 1. Aqueous epoxy sizing agents consisting of an aqueous epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyethylene solution with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37% are used to impregnate alumina fiber filaments. This can achieve a 4K continuous alumina fiber tow fuzzing amount of ≤1.3mg / 50m, reduce the waste rate, increase the utilization rate, and improve the quality and strength of the prepreg; the optimal concentration range of conventional carbon fiber epoxy sizing agents is 0.5% to 1.2%. The low thermal conductivity type γ-Al2O3 continuous alumina fiber of this application has a loose crystal phase, and the optimal concentration range is 1.2% to 1.5%.
[0066] 2. The existing winding machine equipment with a price of about RMB 100,000 to 200,000 can be used in conjunction with the designed roller tooling and flat tooling molds. The cost is low and no expensive yarn spreading dry prepreg equipment is required. The width can be flexibly customized according to small batch tests, such as 300mm width, 400mm width, etc., without being limited by the width of professional prepreg equipment, such as 1000mm.
[0067] 3. Both wet winding low-viscosity resin and conventional standard professional prepreg resin can be used, and the resin selection is flexible;
[0068] 4. It can quickly prepare small batches of test pieces and products for testing the basic mechanical and thermal properties of resin-based alumina composites, as well as for resin selection and matching, fiber performance confirmation, and iterative optimization of composite interface bonding performance. It is suitable for rapid iterative testing in the early pre-research stage. From material preparation to composite sample preparation, it can be completed within 1-2 weeks.
[0069] 5. The use of autoclave molding makes the composite layers denser, the interlayer strength is improved, the interlayer strength is maximized, the overall defects are few, the porosity can be controlled to within 2-4%, there are no defects such as delamination and looseness, the mechanical properties are high, and it is suitable for the preparation of main load-bearing structures;
[0070] 6. The formed resin alumina composite material AluminaFRP has high mechanical properties and strong ultra-low temperature thermal insulation performance. It can replace traditional CFRP and GFRP and is very suitable for the preparation of thermal insulation support structures for low-temperature and deep-cold application scenarios such as superconducting electromagnetic equipment.
[0071] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0072] In the description of the present invention, it should be understood that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "horizontal, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention; the directional words "inside and outside" refer to the inside and outside relative to the outline of each component itself.
[0073] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used herein to describe the spatial positional relationship of a device or feature to other devices or features as shown in the figures. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figures. For example, if the device in the drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.
[0074] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0075] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A rapid preparation method for a deep-cold-resistant, low-thermal-conductivity alumina fiber resin-based composite material, characterized in that: The method comprises: Alumina fiber filaments are subjected to multi-gradient sintering and cooled to a first preset temperature, and the cooled alumina fiber filaments are infiltrated with a water-based epoxy sizing agent. After the infiltration is completed, the alumina fiber filaments are dried to obtain alumina fiber filaments with a resin layer wrapped on the surface; wherein the water-based epoxy sizing agent is composed of a water-based epoxy emulsion with a solution concentration range of 1.2% to 1.5%, or is composed of polyvinyl alcohol with a mass content range of 0.6% to 0.8% and a solution concentration range of 3% to 4% and a polyethylene solution with a mass content range of 0.7% to 0.9% and a solution concentration range of 35% to 37%, and the solvent is water; during the infiltration process, the wire speed range is 1 to 1.5 m / min, and the water-based epoxy sizing agent is kept in a uniformly mixed state by stirring; during the drying process, the drying temperature range is 148° C. to 155° C., and the drying time range is 3 to 5 minutes; Alumina fiber filaments coated with a resin layer are subjected to twist-free spinning to obtain flat-head fiber bundles; A drum with a preset diameter is mounted on a drum-type arrangement machine, and a release paper or liner is laid on the outer surface of the drum; a flat-head fiber tow is spirally wound on the drum with the release paper or liner to obtain a wound drum tow; Use multi-component resin mix or single-component resin as prepreg film or ready-to-dip; The prepreg film is laminated with the drum tow wound on the drum for dipping, and then hot-pressed to achieve semi-curing treatment; or the drum tow wound on the drum is placed in the prepared dipping glue and rotated, and the surface of the drum tow is brushed with glue to ensure uniform bonding of the fibers and the glue, and then placed in an oven for semi-curing treatment according to the preset temperature and time; After the semi-curing treatment, PE film paper is pasted on the outer surface of the drum tow, and the drum tow is cut along the drum generatrix to obtain prepreg; A plurality of prepregs of preset shapes are cut out from the prepreg cooled to a second preset temperature, the cut prepregs are laid out according to preset laying angles and numbers of layers, and the laid prepregs are cured to obtain an alumina fiber resin-based composite material.
2. The method according to claim 1, characterized in that The thickness of the resin layer on the surface of the alumina fiber filaments is greater than that of the carbon fiber and the glass fiber.
3. The method according to claim 1, characterized in that The alumina fiber filaments are low-temperature alumina fiber filaments, the temperature range of the low-temperature alumina fiber filaments is -269 to -100°C, and the density range is 3.2-3.4g / cm 3 , diameter range is 11-14μm, and elongation at break range is 0.75~0.85%.
4. The method according to claim 1, wherein The width of the flat head fiber tow ranges from 3 to 5 mm, and the tow range is 0.1 to 4K.
5. The method according to claim 1, wherein The surface of the demoulding paper or release paper is coated with an isolation material.
6. The method according to claim 1, characterized in that During the winding process, if there is a defective tow, determine whether the length of the defective position is greater than the circumference of the drum. If so, cut off the defective tow and restart the winding. Otherwise, continue winding and mark the defective position. Avoid the marked defective position when cutting the prepreg.
7. The method according to claim 1, characterized in that The multi-component resin includes a low-viscosity resin and a normal-viscosity resin, wherein the viscosity of the low-viscosity resin is in the range of 200 to 1000 mPa·s, and the viscosity of the normal-viscosity resin is in the range of greater than 1000 mPa·s.
8. The method according to claim 1, characterized in that Cutting a plurality of prepregs of preset shapes from the prepreg, laying the cut prepregs according to a preset ply angle and number of layers, and curing the laid prepregs to obtain an alumina fiber resin-based composite material, including: Cutting a plurality of prepregs of preset shapes from the prepreg; Perform surface treatment on the two molds of preset shapes and apply release agent or lay release cloth; Tear off the release paper or liner from the cut prepregs and lay them layer by layer on one of the molds according to the preset laying angle. During the laying process, press each layer evenly with a flat plate or a tool that fits the shape, tear off the PE film on the other side, and continue laying. After laying every 5-10 layers, use a vacuum bag to evacuate the air between the layers and press them tightly and evenly. After the prepreg is laid out and evacuated with a vacuum bag, another mold cover is placed on the upper surface and placed in an autoclave for curing. After the curing is completed, the mold is removed to obtain an alumina fiber resin-based composite material.
9. A deep-cold-resistant, low-thermal-conductivity alumina fiber resin-based composite material, characterized in that: The deep-cold-resistant and low-thermal-conductivity alumina fiber resin-based composite material is prepared by the method described in any one of claims 1-8.